Assessment of endophytic bacteria for suppression of Ralstonia solanacearum growth invitro - Abdul Hamid, Nurayuni (2016)
Banana (Musa spp.) is an important fruit crop Malaysia and grown for fresh and process fruits. Bacterial wilt disease or Moko caused by Ralstonia solanacearum is one of a serious diseases in bananas and plantains cultivation worldwide. Although it is a major threat to the banana cultivation, there is no effective control measure has been developed against it yet. In view of this research was conducted i) to isolate R. solanacearum, the causal pathogen of the bacterial wilt disease and ii) to screen endophytic bacteria for the selection of effective biocontrol agents. Diseased samples were taken from the areas that has been reported was infected by the disease in Johor. The bacterial pathogen was isolated using Kelman’s Selective Media, Tetrazolium chloride (TZC) Medium and subsequently maintained onto Casamino acid-Peptone-Glucose (CPG) medium. Antagonistic bacteria were screen invitro by using agar diffusion well test. There are ninety eight endophytic bacteria were screened for their antibacterial activity against R. solanacearum by measuring the inhibition zone. At the end of study, only one isolate was found suppress the growth of R. solanacearum invitro. However, the isolate is not susceptible to be chosen as one of the effective biological control against the pathogen, R. solanacearum.